2019
DOI: 10.1186/s12864-019-6110-6
|View full text |Cite
|
Sign up to set email alerts
|

Insight into genetic regulation of miRNA in mouse brain

Abstract: Backgroundmicro RNA (miRNA) are important regulators of gene expression and may influence phenotypes and disease traits. The connection between genetics and miRNA expression can be determined through expression quantitative loci (eQTL) analysis, which has been extensively used in a variety of tissues, and in both human and model organisms. miRNA play an important role in brain-related diseases, but eQTL studies of miRNA in brain tissue are limited. We aim to catalog miRNA eQTL in brain tissue using miRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Moreover, the average genomic heritability estimates were slightly higher for mRNA compared to miRNA. In addition, eQTLs of miRNAs or mRNAs in cis dominated compared to trans eQTLs in terms of number and significance, which is consistent with other studies [16,23].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the average genomic heritability estimates were slightly higher for mRNA compared to miRNA. In addition, eQTLs of miRNAs or mRNAs in cis dominated compared to trans eQTLs in terms of number and significance, which is consistent with other studies [16,23].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, chronic morphine SA upregulated mir‐32‐5p in the NAc of male animals 1D after the last drug session (Kim et al, 2018). Indeed, a study of miRNA expression quantitative loci (eQTL) in the mouse brain identified the genomic region of mir‐32‐3p as a significant eQTL and reported that addiction pathways are enriched in mir‐32 predicted target genes, including ‘morphine addiction’ (Kordas et al, 2019). Our data demonstrate a link between NAc mir‐32‐5p levels only after 1D of abstinence, only in the absence of cue exposure, and active lever pressing on the final day of morphine SA.…”
Section: Discussionmentioning
confidence: 99%
“…As in our previous study, a higher number of eQTL were identified for mRNAs than for miRNAs. Moreover, for mRNAs, cis-eQTL dominated trans-eQTL in terms of number and significance [19,21,68]. More than 300 annotated mRNA transcripts showed an eQTL effect and more than 80% were cis-eQTL.…”
Section: Discussionmentioning
confidence: 99%